Lentivirus-based production of human chimeric antigen receptor macrophages from peripheral blood - Ji U Choi; Yeongrin Kim; Da Yeon Lee; Jin Song Park; Moonjung Jeun; Heung Kyoung Lee; Chi Hoon Park (Biomarker Research)
Abstract Although chimeric antigen receptor (CAR) T cell therapy has shown remarkable efficacy against leukemic cells, it still has critical limitations. CAR macrophage has been regarded as a potential alternative to CAR T cells. However, due to the difficulties in gene transduction into macrophages, the production of primary human CAR macrophages from peripheral blood mononuclear cells (PBMC) using lentivirus is highly challenging. Here, we report on how to generate CAR macrophages from human PBMC with lentiviral particles. Using our lentiviral protocol, we produced functional CAR macrophages to lyse and phagocytose target cancer cells efficiently.